Obligatory Wills for Adopted Children, Children of Unmarried Couples, and Children of Different Religions - Muhibbin, Mohammad (Al-Risalah, 2018)
In the perspective of Islamic law, the realization of obligatory wills is along with Islamic insight as a religion which focuses on realizing such realization from the principal of justice and a form of love among human being. This passion which has been created in one family can be realized by the giving of some part of the inheritance through obligatory wills to obstructed people being (heirs), both obstructed as adopted, born outside of legal marriage or children of different religions. All of those are meant for kindness, harmony and to avoid conflicts in the world which give big impact for creating harmony and peaceful family. This research was analysis the application of obligatory testaments to adopted children, legitimate children that born outside of marriage and children of different religions. Analysis has been reviewed according to fiqh’s view, Compilation of Islamic Law (KHI) and practice in the Religious Courts.